Bone surrogates provide authentic onlay graft fixation torques. (March 2019) - Hollensteiner, Marianne; Augat, Peter; Fürst, David; Schrödl, Falk; Esterer, Benjamin; Gabauer, Stefan; Schrempf, Andreas
Abstract: Onlay graft bone augmentation is a standard practice to restore the loss of height of the alveolar ridge following loss of a tooth. Cranial grafts, lifted from the parietal bone, are sandwiched and used to bridge the bony defect in the jaw by means of small screws. During the elevation of the covering gum and subsequent screw placement, care has to be taken in order to preserve underlying nerves. Therefore, to avoid harm to the patient, a solid education of surgeons is essential, which requires training and experience. A simulator for cranial graft-lift training was already developed and shall be expanded to train the augmentation of the lifted implants. Therefore, in this study, synthetic bones for onlay block graft screw placement with realistic haptics for the screw application training were evaluated and compared with human specimens. Six different polyurethane based bone surrogate composites, enriched with varying amounts of calcium-based mineral fillers and blowing agents, were developed. The haptical properties of these synthetic bones were validated for screw placement and compared with human parietal bone specimens. For that, bones were pre-drilled, screws were automatically inserted using a customized testbench and the slope of the screw-insertion torques were analyzed. The slope of the screw insertion torques of the human reference bones was 56.5 ± 14.0 * 10 -3 Nm/deg, Surrogates with lower amounts of mineral fillers and blowing agents showed lower torques than the human bone. Synthetic bones, validated for drilling, milling and sawing in an earlier study, also achieved significantly lower torques, which were only the half of the human parietal bones. Two intermediate stages of the aforementioned material compositions, consisting of 75% mineral filler with 0.75% blowing agent and 100% mineral filler with 1.00% blowing agent revealed results comparable with human bone (57.4 ± 10.2 *10 -3 Nm/deg, p = 0.893 and 54.9 ± 11.1 *10 -3 Nm/deg, p = 0.795, respectively). In conclusion, our findings suggest that, two newly developed polyurethane-based materials mimicking the haptical properties of an onlay bone graft screw fixation, have been identified. Thus, these surrogates are capable of mimicking real bone tissue in our simulator for the education of novice surgeons.